Gas, guns, and governments: Financial costs of anti-ESG policies - Daniel G. Garrett; Ivan T. Ivanov (Federal Reserve Bank of Chicago, 2023)
We study how regulation limiting ESG policies distorts financial market outcomes. In 2021 Texas enacted laws that prohibit municipalities from contracting with banks with certain ESG policies, leading to the exit of five of the largest municipal bond underwriters from the state. Issuers previously reliant on these underwriters face higher uncertainty and borrowing costs since the enactment of the laws. These effects are consistent with a deterioration in underwriter competition as issuers face fewer potential underwriters. Texas issuers will incur 300- 500 million in additional interest on the 31.8 billion borrowed during the first eight months following enactment.
Keywords: 330; ESG Policies; Public Finance; Municipal Bonds; Banking Competition